2016
DOI: 10.1186/s12913-016-1530-3
|View full text |Cite
|
Sign up to set email alerts
|

Occupational physicians’ perceived barriers and suggested solutions to improve adherence to a guideline on mental health problems: analysis of a peer group training

Abstract: BackgroundDespite the impact of mental health problems on sickness absence, only few occupational health guidelines addressing these problems are available. Moreover, adherence has found to be suboptimal. To improve adherence to the Dutch guideline on mental health problems a training was developed for Dutch occupational physicians (OPs) focusing on identifying barriers and addressing them. The aim of this study was to provide an overview of the barriers that OPs perceived in adhering to the Dutch guideline on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 28 publications
0
31
0
2
Order By: Relevance
“…reported in other studies [13,15,17,18] and should be addressed when implementing the program more broadly. With regard to "lack of time," for example, the short duration of the training program makes it feasible; a relatively limited amount of time is required to attend the training program.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…reported in other studies [13,15,17,18] and should be addressed when implementing the program more broadly. With regard to "lack of time," for example, the short duration of the training program makes it feasible; a relatively limited amount of time is required to attend the training program.…”
Section: Methodsmentioning
confidence: 86%
“…Although adherence to guidelines allows for evidence-based best practice and has been shown to improve quality of care [13,14], implementing new guidelines is still challenging [15,16]. Numerous studies have revealed barriers at the organizational, patient or professional level, such as lack of knowledge on the part of individual healthcare physicians [13,15,17,18]. A range of approaches can be taken to address these knowledge gaps, such as educational interventions [13,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Vervolgens werden deze letterlijk uitgeschreven en door twee onderzoekers met behulp van het kwalita tieve softwareprogramma Atlas.ti geanalyseerd. 10 Er werd gekozen om in eerste instantie 50% van de transcripten kwalitatief te analyseren en vervolgens na te gaan of er geen nieuwe inzichten meer werden bereikt (ofwel of er datasaturatie was bereikt, in termen van kwalitatief onderzoek). Dit bleek inderdaad het geval; de overlap in barrières en oplossingen was groot.…”
Section: Data Analyseunclassified
“…Meer gede tailleerde informatie over de analyses is te vinden in het Engelstalige artikel. 10 Resultaten De 31 bedrijfsartsen volgden alle acht bijeenkomsten van de training. Zes bedrijfsartsen konden één keer niet aanwezig zijn en haalden deze bijeenkomst in een andere trainingsgroep in.…”
Section: Data Analyseunclassified
“…Their provision of care and support is pivotal to recovery and the ability to work [9,11]. In the work environment, occupational health physicians and therapists also contribute to workers' health and wellbeing by providing advice on mental health care and promotion [12][13][14][15]. A study using the Delphi method by Dekkers-Sánchez and colleagues suggest that occupational physicians and rehabilitations physicians have relevant role in work retention and return to work of employees [11].…”
mentioning
confidence: 99%